The Competitiveness of Indonesian Cashew Nuts in The Global Market (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
Indonesia is one of the best quality cashew nut producers and exporters with a 1.2% share in the global market. This is very far from being compared to Vietnam as the world's main exporter of cashew nut controlling 34.07% of the global export market. This study aims to determine the competitive and comparative advantages of cashew nuts from Indonesia and Vietnam in the international market at 2009-2018. The various differences between the two countries make the products produced and distributed vary in quality and quantity. Competitive advantage is analyzed using Porter's diamond theory which consists of four factors to see the competitive advantage of an industry/country. Meanwhile, to determine the comparative advantage of cashew nut trading activities, the Revealed Comparative Advantage (RCA) and Trade Specialization Index (ISP) were calculated. Based on the results of the analysis, it can be seen that Indonesia has an advantage in producing cashew nuts, but has not been able to process it optimally, such as Vietnam which applies special technology and standards in producing cashew nuts. The RCA calculation shows that Vietnam's cashew nut exports have much greater competitiveness than Indonesia, and the ISP calculation results show that both exporters are still importing to maintain the economy and ensure the availability of industrial raw materials in the global market. Trade-related policies need to be considered in order to increase export profits and benefit domestic business actors